Bedload transport measurements on the Maros river, Hungary - Kiss, Tímea; Amissah, Gabriel J.; Mezősi, Gábor; Fiala, Károly; Sipos, György (Acta Geographica Debrecina Landscape & Environment series, 2021)
Sediment transport is a vital component in hydrological and fluvial geomorphological studies, however, the temporal and spatial changes in sediment fluxes, and the efficiency of bedload samplers are rarely analysed, as bedload measurements are quite difficult. The aim of the present study is to measure the bedload transport of the sand-bedded Maros River (Hungary) at low stages using the Helley-Smith bedload sampler. In order to understand the variability in the bedload transport, the water stage and discharge across the channel section were also measured. The variability of the bedload was caused by an active in-channel bar and translational sediment pulses. The created bedload transport rating curve could be applied just below 300 m3/s water discharge thus further measurements are needed to evaluate the bedload transport of higher discharges.